Eksistensi gosip di media sosial dalam menentukan return saham di bursa efek indonesia dan persistensi pengaruhnya bersama hari bursa - Widoatmodjo, Sawidji; Siswanto, Halim Putera (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
It isn’t easy to define whether a stock return is determined by a certain factor or trading days. There were many research evidence that some factors had influenced stock return. There were also, however, many researches on stock return anomaly providing the facts that stock return, especially their abnormal returns, were caused by specific trading days, such as week-day effect, January effect, and many others. This research attempts to explore this logic. We tested the impact of gossips that spreaded-out through social media, as a certain factor, and all trading days in a week to a stock return. We used the gossips in social media as response of the massive use of the internet in stock investment. The existence of the gossips is more strengthened by the existence of noise traders. Nowadays, noise traders use the internet, such as mailing list, message board, facebook, and others, that are called as social media, as a media to spread gossips. This research investigates whether gossips spreaded through mailing list have a role in mispricing, so then it can be used to determine the stock return. If they have the role, then how long is the persistence? To anticipate the impact of trading days, this research also includes trading days as a control variable. Using multivariate statistical technique and combined with event study with five windows (five days before and after a gossip has been posted), this research analyzes the stock return that gets the most gossips posted by investors. The result suggests that the gossips in social media don’t show significant influence on the stock return, and automatically no persistence exists. Based on that result, the conclusion is that the gossips in social media can’t be used to determine the stock return. The implication is that even social media can facilitate the stock transaction better, the investors in Indonesia Stock Exchange can’t exploit the gossips in social media for taking profit through behaving as noise traders.